Integrated nutrient management on performance of wheat (Triticum aestivum L.) - Dhaka, B.R.; Chawla, Nitin; Pathan, A.R.K. (Annals of Agricultural Research, 2014)
The experiment was conducted at Agricultural Research Station, Durgapura, Jaipur during 2006-07, 2007-08. The results showed that the application of 120 kg N + 40 kg P2O5/ha and poultry manure @ 6t/ha by broadcasting recorded the maximum number of effective tillers, grains per ear, ear length, 1,000 grain weight, grain, straw and biological yields of wheat. The extent of increase in grain and straw yield was 49.51 and 46.64 per cent with the application of 120 kg N + 40 kg P2O5/ha over lowest level. The extent of increase in grain and straw yield was 49.5 and 46.6 per cent with the application of 120 kg N + 40 kg P2O5/ha and 55.5 and 42.3 per cent with the application of poultry manure @ 6t/ha by broad casting. A pot experiment of organic amendment on survival of bio-agent in soil was also planned; the results indicated that the efficacy of bio-agent increased the soil due to application of organic amendment. The population of Triticum harzianum was significantly higher in soils amended with farm yard manure, vermin-compost or mustard cake.